The relationship between Total Quality management and Industry 4.0: a framework proposal - Barbosa Silva, Kayke Augusto; Amorim Santos, Paulo Henrique; dos Reis Pereira Maia, Daniele; Sanjulião, Lo-Ruana Karen Amorim Freire (Brazilian Journal of Production Engineering, 2026)
The potential of the Fourth Industrial Revolution is being investigated simultaneously with its ongoing evolution. In this emerging context, there is a growing need for studies that integrate Total Quality Management (TQM) principles with Industry 4.0 technologies. This article aims to propose a theoretical model linking TQM concepts with the technological enablers of Industry 4.0. To achieve this, a Systematic Literature Review (SLR) was conducted, complemented by descriptive bibliometrics and social network analysis techniques, to identify key relationships, research gaps, and field trends. The results reveal a significant increase in scientific output since 2019, with emphasis on studies exploring Big Data Analytics, Artificial Intelligence, and digital integration in quality systems. The proposed theoretical model provides a conceptual foundation for future empirical investigations and offers practical guidance for industrial managers seeking to align quality practices with the industry 4.0 paradigm.